Kernel morphometric traits in hexaploid wheat (Triticum aestivum L.) are modulated by intricate QTL x QTL and genotype x environment interactions - Prashant, Ramya; Kadoo, Narendra Y.; Desale, Charushila; Kore, Prajakta; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Gupta, Vidya (Journal of Cereal Science, 2012)
Wheat kernel size and shape influence its flour yield and market price. A hexaploid wheat population of 185 recombinant inbred lines was evaluated for five kernel morphometric traits namely, 1000-kernel weight, kernel length, width, length width ratio and factor form density in two diverse agro-climatic regions in India in five to eight year location combinations. Additive main effects and multiplicative interaction analysis revealed significant contributions from genotype (G) and genotype x environment (G x E) effects for these traits. Quantitative trait locus (QTL) analysis by composite interval mapping (CIM) was performed using a linkage map of 251 SSR markers and 59 QTLs distributed on 16 chromosomes were identified. The majority of the QTLs were located on the D genome (44.07%) and the homeologous chromosomes of Group 2 (38.98%). Stable QTLs detected in three or more year location combinations were identified for four traits. Multi-trait CIM showed 10 chromosomal regions harboring putative pleiotropic loci. Complexity in the genetic effects was further revealed by QTL analysis based on mixed-linear model that indicated 19 QTLs with significant individual effects (main-effect QTLs) and 14 QTL x QTL interactions. Five of these - nineteen main-effect QTLs and one of the fourteen QTL x QTL interactions showed environmental influence. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Epistatic QTLs; Genotype x environment interactions; Kernel size and shape; Stable QTLs